Soap: Touching objects, feeling critique in critical global health studies (Medicine Anthropology Theory, 2019)
Anthropology has long grappled with the politics of critique. In critical global health studies, an emerging subfield of medical anthropology with roots in histories and geographies of colonial and international health, ethnographers negotiate relations and transactions in the field that pivot around boundaries at the core of our disciplinary practice: inside/outside, critique/complicity, theoretical/applied. Yet, while critique is a primary endeavor of the anthropologist, few have explicitly analyzed or reflected on its meanings, valences, affects, and entailments, particularly amid the rise of global health and the NGOization of the global South that inflects much of our work. In this essay, I reflect on the state of critique in critical global health studies, sketching its gestures, rhetoric, and intentions. Then, I trace some of the journeys of the bar of soap pictured below, an object that touched me in many senses of the term by intersecting, facilitating, and holding my anthropological interest for over a decade. Finally, drawing on recent feminist science studies scholarship, I suggest that critique, as entangled and entangling practice, is a form of care that might productively reframe anthropologists’ normative aspirations to ‘usefulness’ or ‘relevance’.